EFFECT OF AZOTOBACTER SP AND UREA FERTILIZER (N) ON EFFICIENCY (N) UPTAKE AS WELL AS TOMATO CROP YIELD - Anatje Lihiang (JUPE : Jurnal Pendidikan Mandala, 2022)
One of the   important  commodities  that are widely  consumed  to  meet  nutritional  and food  needs,   especially  vegetables,   is  tomato  (Solanum lycopersium).  The need for  tomatoes  is increasing    both  in  quantity  and  quality.  But  until  now   the   need for   vegetables  in  quantity  and  quality  is difficult to   meet  using    conventional  agriculture.  For this  reason, the     application of biological fertilizers   that have the potential to  reduce the use of   inorganic  fertilizers  and are able to  efficiently  fertilize, namely      the use of  Azotobackter  sp.    The ability of   these  microbes  to  tether  nitrogen from  the air  largely depends  on   environmental conditions, especially the   availability of  organic  matter within  the   rhizosphere, aeration  and   soil moisture  .   Nitrogen is  a very important plant  nutrient.  The adequacy of the   supply of   nitrogen in plants  is characterized  by the   speed of  plant growth    and   dark  green leaf color.   In  the research of   Goeswono  Soepardi  (1983), stated  that  nitrogen tethering  by Azotobacter  sp  is only  about  25 kh  ha-1  N year-1.  Meanwhile, the   need for  nitrogen in   tomato plants  according to   Tisdale et al  (1985) is  82-120 kg ha-1  N  to   be able to  produce  about  30 tons of    ha-1 fresh   tomatoes .  This situation    shows  that  to  meet the   needs of  tomato  plants  for nitrogen, nitrogen   fertilization is still  needed even though they   have  received  additional    nitrogen   from  Azotobacter  inoculated sp, that is,   by  fertilizing  urea as  a source of  N.   The objectives of  this  study  are: 1.  Effect of  Azotobacter  sp  and   nitrogen fertilizers on N   uptake  by plants as   well as  tomato  crop   yield, 2.  The dose of nitrogen   fertilizer  on  the inoculation of   Azotobacter  sp  that gives  the highest tomato yield    .   Based on  the results   of the   research obtained , there was a noticeable  increase in N   uptake  in  the administration of   Asotobakter  sp  inoculant  treatment  and accompanied by      the  application of  nitrogen  fertilizers    than  those that were not  given   Asotobakter  sp  inoculants  and   nitrogen fertilizers  on each  treatment. The highest yield of fresh   tomatoes  was  found in the   A1N3 treatment with a     fresh   weight of   tomato fruits of   8,969.30 g / plant  with  a dose of nitrogen     fertilizer  90 kg